The Impact of Asthma Education Programs on Children's Life Aspects: A Systematic Review - Alreshidi, Nashi; Al-Kalaldeh, Mahmoud (Current Respiratory Medicine Reviews, 2021)
Objective: This Scoping review was conducted to explore the impact of education programs on asthmatic children's knowledge of asthma, quality of life, school absenteeism, and selfmanagement. Data Sources: The Scoping review was restricted to randomized controlled trials and quasi-experimental designs. Studies published in the English language between 2000 and 2017 were retrieved from CINAHL, MEDLINE, OvidSP, Cochrane Library, ProQuest, and Google Scholar databases. Studies Selection: Along with specific inclusion and exclusion criteria for selecting studies, an evaluation for the quality of the experimental research based on the level of evidence was applied to categorize studies into poor to good quality. Results: Of the 1256 items initially identified references, 18 studies were included in the review to cover the impact of asthma education on four major areas: children's knowledge of asthma, quality of life, school absenteeism, and self-management. Conclusion: Despite some inconsistencies between the reviewed studies, asthma education programs demonstrated a positive effect on children's knowledge of asthma, quality of life, school absenteeism, and self-management. Further research on the effect of asthma education on children's activity level, symptoms, and emotional domains is warranted.
Keywords: Asthma education